A quantitative analysis of factors which influence supplement use and doping among adolescent athletes in New Zealand - Clancy, Sian; Borotkanics, Robert; Millar, Sarah-Kate; Oldham, Anthony R. H. (Frontiers in Sports and Active Living, 2023)
Objectives. Doping is a maladaptive behaviour which poses numerous risks and potentially enhances athletic performance while supplement use poses threats of positive, yet inadvertent, doping control results. Investigation is required to understand factors that influence adolescent supplement use and doping in New Zealand (NZ). Design. A survey was completed by 660 athletes aged 13 to 18 years, of any gender, who competed at any level of any sport in NZ. Forty-three independent variables measured autonomy, confidence sources, motivational climate, social norms and age. Methods. Multivariate, ordinal, and binary logistic regression models measured associations between independent variables and five dependant variables: supplement use, doping, doping considerations and intent (soon and in the next year). Results. Confidence through mastery, internally perceived locus of control (IPLOC) and volition decreased the odds of doping while confidence through self-presentation, subjective and descriptive norms increased the odds of supplement use and doping. Conclusion. To decrease the odds of doping, adolescent autonomy should be increased in sport through opportunities for volitional decision making and exposure to mastery as a confidence source.